How can we reduce maternal mortality due to preeclampsia? The 4P rule - Korkes, Henri Augusto; Cavalli, Ricardo Carvalho; Oliveira, Leandro Gustavo de; Ramos, José Geraldo Lopes; de Almeida Martins Costa, Sérgio Hofmeister; de Sousa, Francisco Lázaro Pereira; da Cunha, Edson Vieira; de Souza Mesquita, Maria Rita; Corrêa, Mário Dias; Araújo, Ana Cristina Pinheiro Fernandes; Zaconeta, Alberto Carlos Moreno; Freire, Carlos Henrique Esteves; et al. (Federação das Associações de Ginecologia e Obstetrícia, 2024)
In low and middle-income countries such as Brazil, most maternal deaths are related to hypertensive complications. Preeclampsia is the leading cause of maternal mortality and morbidity. Significant proportion is associated with the following factors: lack of identification of high-risk women, lack of adequate prevention, difficulty in maintaining a high-risk prenatal follow-up, delayed diagnosis, insecurity and low use of magnesium sulphate, delayed pregnancy interruption and lack of postpartum follow-up of these high-risk cases. Four major actions are proposed to minimize this alarming clinical picture and reduce the mortality rates due to preeclampsia, called the "4 P Rule" (Adequate Prevention - Vigilant Prenatal Care - Timely Delivery (Parturition) - Safe Postpartum). From this simple "rule" we can open a range of important processes and reminders that may help in the guidance of preeclampsia management.